Effectiveness of magnetocardiography as a non-invasive tool for functional assessment of myocardial ischemia in patients with stable coronary artery disease - Wen-fei He; Li-huan Zeng; Nan-shan Xie; Hao-xing Liu; Hao-xing Liu; Wen-min Cui; Ying Wang; Zhi-jian Zhang; Guan-lun Ye; Zhi-ying Qin; Zhi-qiang Guo; Jun Ma; et al. (Frontiers in Medical Technology)
BackgroundIdentification of coronary ischemia in suspected coronary artery disease (CAD) remains challenging. Magnetocardiography (MCG) demonstrated comparably high diagnostic efficiency for detecting coronary ischemia in previous studies. However, limited evidence exists comparing MCG vs. computed tomography angiography-derived fractional flow reserve (CTFFR) in suspected CAD patients.MethodsA total of 291 patients with CTA-confirmed diameter stenosis ranging from 30% to 90% were included and divided into two groups based on the CTFFR values, the stable coronary artery disease (SCAD) group (≤0.8) and the non-SCAD group (>0.8). Magnetic field map (MFM) parameters were employed to construct a diagnostic model. The performance of the models was evaluated using receiver operating characteristic (ROC) curves, accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV).ResultsPatients with SCAD showed a mean MCG score of 5.6 ± 2.9, while the non-SCAD group demonstrated a mean score of 2.0 ± 1.9 (P < 0.001). The area under the curve (AUC) for ROC analysis was 0.824 (95% CI: 0.772–0.877). Point 5 was selected as the operational cutoff value providing a favorable balance of sensitivity and specificity. Ultimately, MCG score yielded a sensitivity of 69.6%, specificity of 87.9%, PPV of 72.7%, NPV of 86.2%, and accuracy of 82.1%.ConclusionsCompared to CTFFR, MCG demonstrated superior specificity and moderate sensitivity for detecting CAD in patients with diameter stenosis CTA ranging from 30% to 90%. It may provide an alternative to functional evaluation prior to invasive or radiation exposure methods.